Acrylamide exposure: Dietary risks of oral carcinoma in non-smokers - Gokul Sudhakaran; Kuppusamy Sathishkumar; Meivelu Moovendhan (Oral Oncology Reports)
Acrylamide, classified as a probable human carcinogen, is primarily found in plant-derived foods like potatoes, grains, and coffee, with heightened formation during high-temperature cooking. Exposure occurs through food and cigarette smoke. Rodent studies indicate an increased cancer risk, with acrylamide converting into glycidamide, causing DNA damage. Its hydrophilic nature allows penetration into various body tissues. Though evidence linking dietary acrylamide intake to head and neck cancer risk is inconclusive, potential exceptions exist. Further research, particularly on non-smokers, is recommended. Minimizing exposure via dietary and cooking modifications is crucial. Additional studies on human acrylamide and oral cancer risk are needed for effective public health strategies.